Measuring and explaining levels of regional economic integration - Jennifer Pédussel Wu (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2004)
124 Regional Trade Agreements were notified to the GATT during the period 1948-1994. Since 1995, over 130 agreements have been notified to the WTO. Using empirical evidence, this paper proposes a way of measuring levels of regional integration and examines several potential explanations for the existence of different levels of regional economic integration. Using a database of regional integration where levels of integration are ranked across countries, a probit analysis in a discrete choice framework is applied. Common traits influencing regional integration decision-making were examined to determine those most influential. It is concluded that democracy and economic freedom, are significant contributors to the chosen level of regional integration. The role of political and economic uncertainty is examined and it is found that trade uncertainty is also a significant contributing factor.
Keywords: F02; F15; C8; C19; 330; Regional Economic Integration; Ordered-Probit Estimation; Uncertainty